Research genetics 2001 catalogue accelerating discovery. (Research Genetics (an Invitrogen Company), 2001)
Introduces cloning and genetic engineering, exploring the technology and social issues involved and looking toward what the future might bring as it becomes possible to duplicate even human DNA.